Signifikansi Mentor dalam Membangkitkan Pemimpin Jemaat - Pieter Anggiat Napitupulu (Sekolah Tinggi Alkitab Penyebaran Injil Majalengka, 2020)
The leader is a determinant in the progress of a church, although it does not neglect other supporting elements of progress. The availability of a leader who is truly ready to lead the congregation is a long conversation from time to time. Although this need is categorized as urgent, many do not understand how to raise up a new leader who has qualified qualifications in the church. Efforts to raise up and bring up leaders in the church is a struggle of its own. The deliberate mentoring process will help equip a subordinate to be ready to become a new leader. A mentor not only has knowledge, but high skills and exemplary living are important things to share with prospective church leaders. The success of mentoring depends more on the quality of the mentor, with careful use of mentoring techniques. On the other hand, it is also expected that obedience and submission of their subordinates during the mentoring process. All of these things become a completeness in making someone appear to be the leader of the church later. Thus the mentoring process becomes significant in church leadership, where new leaders will rise up with high qualities that bring the congregation to progress. Abstrak Pemimpin merupakan penentu dalam kemajuan suatu jemaat, walaupun tidak mengabaikan elemen-elemen penunjang kemajuanlainnya. Ketersediaan seorang pemimpin yang benar-benar siap pakai dalam memimpin jemaat merupakan percakapan panjang dari masa ke masa. Walau kebetuhan ini tergategori mendesak, namun banyak yang kurang memahami bagaimana cara membangkitkan seorang pemimpin yang baru yang memiliki kualifikasi yang mumpuni di dalam jemaat. Upaya membangkitkan dan memunculkan pemimpin di jemaat meru-pakan pergumulan tersendiri. Proses mentoring yang dilakukan secara sengaja akan menolong dalam melengkapi seorang bawahan untuk kelak siap menjadi pemimpin yang baru. Seorang mentor bukan saja memiliki pengetahuan, namun skill yang tinggi dan keteladanan hidup merupakan hal penting untuk dibagikan kepada calon pemimpin jemaat. Keberhasilah mentoring lebih bergantung pada kualitas mentor, dengan kecermatan menggunakan tehnik mentoring. Di sisi lain juga diharapkan ketaatan dan ketundukan bawahannya selama proses mentoring. Semua hal ini menjadi suatu kelengkapan dalam menjadikan seseorang muncul menjadi pemimpin jemaat kelak. Demikianlah proses mentoring menjadi signifikan dalam kepemimpinan jemaat, di mana pemimpin baru akan bangkit dengan kualitas tinggi yang membawa jemaat kepada kemajuan.